2011
DOI: 10.1002/polb.22353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular weight on the short‐channel effect in polymer‐based field‐effect transistors

Abstract: In this study, we demonstrate how the intrinsic properties of a polymer can influence the electrical characteristics of organic field-effect transistors (OFETs). OFETs fabricated with three batches of poly[2-methoxy,5-(3 0 ,7 0 -dimethyl-octyloxy)]p-phenylene vinylene (MDMO-PPV) were investigated. The properties of the polymers were initially investigated using Fourier transform infrared spectroscopy (FTIR), impedance spectroscopy (IS), gel permeation chromotography (GPC), and cyclic voltammetry (CV), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Solution processable thin-film organic electronic devices, such as planar perovskite solar cells (PSCs), organic photovoltaic solar cells (OPVs), organic light emitting diodes (OLEDs), , and organic field-effect transistors (OFETs), hold excellent promise as lightweight, flexible, and cost-effective devices. Low temperature solution processing of thin films of active materials, employing spin coating and spray coating, is a cost-effective and high-throughput technique for fabrication of electronic devices. , However, the reliability and reproducibility of solution-processed thin films as well as controlling the resulting morphology poses a significant challenge .…”
Section: Introductionmentioning
confidence: 99%
“…Solution processable thin-film organic electronic devices, such as planar perovskite solar cells (PSCs), organic photovoltaic solar cells (OPVs), organic light emitting diodes (OLEDs), , and organic field-effect transistors (OFETs), hold excellent promise as lightweight, flexible, and cost-effective devices. Low temperature solution processing of thin films of active materials, employing spin coating and spray coating, is a cost-effective and high-throughput technique for fabrication of electronic devices. , However, the reliability and reproducibility of solution-processed thin films as well as controlling the resulting morphology poses a significant challenge .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some recent studies have begun to observe that the molecular weight and the alkyl substituent of a given polymer platform have a profound influence on molecular ordering and microstructure, and additionally on optoelectronic and charge transport characteristics, thus making it one of the key parameters governing the device performance. , For example, it was found that not only increasing the molecular weight but also decreasing the distance of the branching point of branched alkyl chains to backbones and their bulkiness and are linked to improved charge transport arising from better intergrain connectivity. , However, in most cases, the effects of molecular weight and alkyl substituent variations on polymer properties and device performances have been studied independently. ,, To the best of our knowledge, there are only a few reports on a structure–property relationship regarding the simultaneous tuning of molecular weight and alkyl substituents, , which has to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effects of molecular weight and polydispersity of the polymers on the PLED performance are still underexplored. Although a few previous studies were conducted, 33,34,126,127 much more work has to be done to gain conclusions of enhanced generalities and also to obtain more solid understanding on the structure-property relationships in PLED materials. In addition, the purity of polymers for PLED applications should always be verified to establish a reliable link between device performances with the structure of the polymer employed in the device.…”
Section: Discussionmentioning
confidence: 99%
“…Polydispersity index (PDI) has a significant impact on the effective conjugation length homogeneity of the polymer chains which in turn affects the emission colors, formation of undesirable charge traps and interchain packing in the polymer. 33,126,127 Fig. 27.…”
Section: Conjugated Versus Non-conjugated Polymers: Materials Preparatmentioning
confidence: 99%